Case Report: Successful Reperfusion of Pulmonary Thromboembolism Using tPA in a Cat - Sutton, Blake; Long Mays, Erin; McLaughlin, Chris (Frontiers in Veterinary Science, 2022)
Pulmonary thromboembolism is a potentially life threatening condition that is uncommonly recognized in cats. Thrombolytic agents have been described as a treatment for this condition in human and canine patients, particularly in cases where hemodynamic instability is persistent despite supportive care. This report describes the clinical course, echocardiographic diagnosis, and successful thrombolysis of a cat with pulmonary thromboembolism. Despite confirmed reperfusion, the cat succumbed to thromboembolic disease highlighting the dearth of knowledge about optimal treatment of this disease process in small animals, particularly in cats.